Hans-Georg Gadamer and spanish philosophy - Martín Gómez, María (Anales del Seminario de Historia de la Filosofía, 2018)
This article develops the relationship between Hans-Georg Gadamer and Spanish philosophers at the end of the 20th century after the completion of a research stay in the Deutsche Literatur Archiv in Marbach. New materials and unpublished correspondence recently found in the Deutsche Literatur Archiv in Marbach reveal common interests and intellectual links between Hans-Georg Gadamer and several Spanish philosophers: Jose Ortega y Gasset, Julián Marías, Laín Entralgo, Xavier Zubiri or Emilio Lledó. The letters, that Gadamer wrote and received, show that the evident dialogical character of Gadamer’s hermeneutic was always one of his most representative characteristics. These unpublished notes are of particular interest in the understanding of the history of philosophy in Spain and the hermeneutical development.
Keywords: Spanish philosophy; iberoamerican philosophy; Hans-Georg Gadamer; hermeneutic.